2023
DOI: 10.1177/20503121231172866
|View full text |Cite
|
Sign up to set email alerts
|

Early detection of cold stress to prevent hypothermia: A narrative review

Abstract: Temperature monitoring is essential for assessing neonates and providing appropriate neonatal thermal care. Thermoneutrality is defined as the environmental temperature range within which the oxygen and metabolic consumptions are minimum to maintain normal body temperature. When neonates are in an environment below thermoneutral temperature, they respond by vasoconstriction to minimise heat losses, followed by a rise in metabolic rate to increase heat production. This condition, physiologically termed cold str… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 49 publications
(63 reference statements)
0
2
0
Order By: Relevance
“…Our study showed that when cold milk is fed orally to preterm infants, it reaches the stomach at an approximate temperature of 83.3 °F, which is above the typical room temperature range (68-77 °F) that is used when milk is introduced directly into the stomach via NGT or OGT feeding methods. [37] Since it was not the focus of our study, we did not investigate the effects of introducing cold milk directly to the stomach via NGT. Our findings are consistent with a study conducted on adult volunteers, which observed that gastric temperatures returned to within 1 degree of core body temperature within 30 minutes of consuming a cold drink.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our study showed that when cold milk is fed orally to preterm infants, it reaches the stomach at an approximate temperature of 83.3 °F, which is above the typical room temperature range (68-77 °F) that is used when milk is introduced directly into the stomach via NGT or OGT feeding methods. [37] Since it was not the focus of our study, we did not investigate the effects of introducing cold milk directly to the stomach via NGT. Our findings are consistent with a study conducted on adult volunteers, which observed that gastric temperatures returned to within 1 degree of core body temperature within 30 minutes of consuming a cold drink.…”
Section: Discussionmentioning
confidence: 99%
“…[31][32][33][34] These studies revealed tolerance to cold feeding with no significant adverse effects on the infants' sleep patterns, vocalizations, motility, intake, feeding behavior, weight gain, temperature, frequency of regurgitation, or gastric emptying time. While previous studies demonstrated the safe use of cold feedings, [31][32][33][34] there are concerns that cold feeding will induce digestive malfunction [35,36] or cold stress associated with an axillary or rectal temperature of 36.0°C-36.4°C [37] and physiological manifestations. Furthermore, preterm infants are at an increased risk of necrotizing enterocolitis and hypothermia, which have been linked to increased risk of adverse neonatal outcomes.…”
Section: Introductionmentioning
confidence: 99%